2022
DOI: 10.3389/fendo.2022.903085
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Composite pheochromocytoma with ganglioneuroma component: A report of three cases

Abstract: Composite pheochromocytoma (CP) is a very rare tumor originating from neural crest cells, predominantly composed of pheochromocytoma (PCC), a chromaffin cell tumor arising in adrenal medulla, and ganglioneuroma, a tumor derived from autonomic ganglion cells of the nervous system. Moreover, CP may be present in the hereditary syndromes of which pheochromocytoma is part. Literature offers scarce data on this subject, and particularly about its biological behavior, clinical evolution, and molecular profile. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, failure to identify these masses can lead to life-threatening complications during surgery [ 12 ], highlighting the need for vigilant pre- and intraoperative blood pressure surveillance even in the setting of normal metanephrine levels. It is worth noting that Araujo et al [ 13 ] (2022) reported three cases of composite pheochromocytoma-ganglioneuroma, which is a rare variant of adrenal ganglioneuroma characterized by the coexistence of a pheochromocytoma and a ganglioneuroma within the same tumor. Patients with composite pheochromocytoma-ganglioneuroma may present with symptoms related to excess catecholamine secretion, similar to those with pheochromocytomas [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, failure to identify these masses can lead to life-threatening complications during surgery [ 12 ], highlighting the need for vigilant pre- and intraoperative blood pressure surveillance even in the setting of normal metanephrine levels. It is worth noting that Araujo et al [ 13 ] (2022) reported three cases of composite pheochromocytoma-ganglioneuroma, which is a rare variant of adrenal ganglioneuroma characterized by the coexistence of a pheochromocytoma and a ganglioneuroma within the same tumor. Patients with composite pheochromocytoma-ganglioneuroma may present with symptoms related to excess catecholamine secretion, similar to those with pheochromocytomas [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Araujo et al [ 13 ] (2022) reported three cases of composite pheochromocytoma-ganglioneuroma, which is a rare variant of adrenal ganglioneuroma characterized by the coexistence of a pheochromocytoma and a ganglioneuroma within the same tumor. Patients with composite pheochromocytoma-ganglioneuroma may present with symptoms related to excess catecholamine secretion, similar to those with pheochromocytomas [ 13 ]. In this case, since there were no histological findings of a pheochromocytoma, including no excess catecholamine secretion, positive staining for chromogranin A, or dopamine beta-hydroxylase, the presence of a composite pheochromocytoma-ganglioneuroma was effectively ruled out.…”
Section: Discussionmentioning
confidence: 99%